School-based intervention for the prevention of HPV among adolescents: a cluster randomised controlled study. Issue 1 (27th January 2016) - Grandahl, Maria; Rosenblad, Andreas; Stenhammar, Christina; Tydén, Tanja; Westerling, Ragnar; Larsson, Margareta; Oscarsson, Marie; Andrae, Bengt; Dalianis, Tina; Nevéus, Tryggve
Abstract : Objective: To improve primary prevention of human papillomavirus (HPV) infection by promoting vaccination and increased condom use among upper secondary school students. Design: Cluster randomised controlled trial. Setting: 18 upper secondary schools in Sweden. Participants: Schools were first randomised to the intervention or the control group, after which individual classes were randomised so as to be included or not. Of the 832 students aged 16 years invited to participate during the regular individual health interview with the school nurse, 751 (90.2%) agreed to participate and 741 (89.1%) students completed the study. Interventions: The intervention was based on the Health Belief Model (HBM). According to HBM, a person's health behaviour can be explained by individual beliefs regarding health actions. School nurses delivered 30 min face-to-face structured information about HPV, including cancer risks and HPV prevention, by propagating condom use and HPV vaccination. Students in the intervention and the control groups completed questionnaires at baseline and after 3 months. Main outcome measures: Intention to use condom with a new partner and beliefs about primary prevention of HPV, and also specifically vaccination status and increased condom use. Results: All statistical analyses were performed at the individual level. The intervention had a significant effect on the intention to use condom (p=0.004). There was also a significant effect on HBM total score (p=0.003), with a 2.559 points higher score for the intervention group compared to the controls. The influence on the HBM parameters susceptibility and severity was also significant (p<0.001 for both variables). The intervention also influenced behaviour: girls in the intervention group chose to have themselves vaccinated to a significantly higher degree than the controls (p=0.02). No harms were reported. Conclusions: The school-based intervention had favourable effects on the beliefs about primary prevention of HPV, and increased the HPV vaccination rates in a diverse population of adolescents. Trial registration number: NCT02280967; Results.